Trends in cardiovascular and bleeding outcomes in acute coronary syndrome patients treated with or without proton-pump inhibitors during the introduction of novel P2Y12 inhibitors: a five-year experience from a single-centre observational registry. Issue 3 (2nd August 2018) - Hoedemaker, Niels P G; Damman, Peter; Ottervanger, Jan Paul; Dambrink, Jan Henk E; Gosselink, A T Marcel; Kedhi, Elvin; Kolkman, Evelien; de Winter, Robbert J; van 't Hof, Arnoud W J
Abstract: Aims: Proton-pump inhibitors (PPIs) are commonly prescribed in acute coronary syndrome (ACS) patients on antiplatelet therapy. We studied PPI prescription in ACS patients in the era of novel P2Y12 inhibitors and assessed the association between PPI use and clinical outcomes. Methods and results: Between 2010 and 2014, we included all consecutive ACS patients admitted to a Dutch tertiary hospital. The main outcome was PPI prescription at discharge. Additionally, we present 1-year mortality and 30-day cardiovascular and bleeding outcomes. Of 4595 ACS patients with known discharge medication, 63.9% received a PPI. PPI-treated patients were older (67.1 ± 12.5 vs. 63.0 ± 13.3, P  < 0.001). PPI treatment at discharge increased from 34.7% in 2010 to 88.7% in 2014 ( P  < 0.001). Concurrently, ticagrelor prescription at discharge increased from 0.0% to 48.6% in 2014 ( P  < 0.001), while clopidogrel prescription decreased from 78.6% in 2010 to 28.7% in 2014 ( P  < 0.001). PPI treatment was associated with reductions in death or myocardial infarction (MI) [adjusted hazard ratio (HR) 0.27, 95% confidence interval (CI) 0.10–0.76] and death, MI or stroke (adjusted HR 0.33, 95% CI 0.14–0.81) at 30-days post-discharge. However, this association was not present in subgroup analyses of patients treated with clopidogrel or ticagrelor. Conclusion: In this single-centre registry, PPI prescription in ACS patients doubled between 2010 and 2014. PPI treatment at discharge was associated with a reduction in death, MI, or stroke at 30-days post-discharge, mainly driven by a reduction in MI. There were no differences gastrointestinal bleeding between patients treated with or without a PPI. PPI treatment may serve as a marker of improved therapies and outcome, rather than causing a reduction in cardiovascular events.